Effect of Relationship Marketing Towards Customer Loyalty in the Lubricant Industry - Christian Rendy Pradana; Agus Baktiono; Rossa Adinda Saputri (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2022)
The pandemic COVID-19 is a global health crisis, but the impacts are on the economics and social aspects. PT Cemako Lestari Indonesia is a company engaged in the lubricant industry trying to maintain customer loyalty through relationship marketing even though the current pandemic conditions are hampering sales activities. This study uses a quantitative approach. The population in this study were 50 customers of PT. Cemako Lestari Indonesia. The sampling technique used was saturated sampling. Data collection was done using Google Forms. The data analysis technique used is the R square test, F test and t test at a significant level of alpha 0.05. The result of this research is relationship marketing has a significant effect on customer loyalty. While the results of partial hypothesis testing indicate that trust, commitment, communication has a significant effect on Customer Loyalty, but the Conflict Handling has no significant effect on Customer Loyalty.